Kedudukan Dan Peran Organisasi Profesi Advokat Terhadap Advokat Yang Berhadapan Dengan Hukum - Endira, Bramedika Kris; Junaidi, Muhammad; Ratna Sediati, Diah Sulistyani; Sihotang, Amri Panahatan (JURNAL USM LAW REVIEW, 2022)
This study aims to determine the role of an advocate organization, in this case: The Indonesian Advocates Association (Peradi) in maintaining the dignity of its advocates who are addressing the law. Sociologically, the advocate profession is a free and independent profession and is responsible for law enforcement. However, juridically, because advocates are "law enforcers", as regulated in Article 5 paragraph 1 of the Advocate Act Number 18/2003, they are obliged to carry out their professional duties to defend cases that are their responsibility by adhering to the professional code of ethics. and laws and regulations. The approach used in this study is a normative juridical approach. This is clearly and evidently regulated in Article 15 of the Advocate Act Number 18/2003. The Indonesian Advocates Association Organization (Peradi) is expected to always be present in maintaining the advocate profession, especially in relation to the Immunity Rights of its advocates. The role of the Advocate organization of the Indonesian Advocates Association (Peradi) must be optimal in maintaining the dignity and prestige of Advocates who are in conflict with the law so that its Advocates are more competent in handling cases.Penelitian ini bertujuan untuk mengetahui sejauh mana peranan Organisasi Advokat dalam hal ini Perhimpunan Advokat Indonesia (Peradi) dalam menjaga marwah dan martabat Advokat yang berhadapan dengan hukum. Secara sosiologis, profesi Advokat adalah profesi yang bebas dan mandiri serta bertanggung jawab dalam penegakan hukum. Namun, secara yuridis, karena Advokat merupakan penegak hukum , sebagaimana diatur di dalam Pasal 5 ayat 1 Undang-undang Advokat Nomor 18 Tahun 2003, maka berkewajiban untuk menjalankan tugas profesinya untuk membela perkara yang menjadi tanggung jawabnya dengan tetap berpegang pada kode etik profesi dan peraturan perundang-undangan. Hal tersebut secara terang dan jelas diatur di dalam Pasal 15 Undang-undang Advokat Nomor 18 Tahun 2003. Pendekatan   yang   digunakan   dalam   penelitian   ini   adalah   pendekatan   yuridis normatif. Hasil penelitian ini menjelaskan bahwa organisasi profesi hadir dalam menjaga profesi Advokat khususnya terkait dengan hak imunitas Advokat. Peranan Organisasi Advokat Perhimpunan Advokat Indonesia (Peradi) harus optimal dalam menjaga marwah dan martabat Advokat yang berhadapan dengan hukum agar para anggotanya lebih berkompeten dalam penanganan perkara.